Módulo de consultoría para la gestión del Centro de Formación Permanente de la PUCE Ibarra - Montesdeoca Maza, Orlidan Duvanny (2025)
This project degree focuses on the development and implementation of a consulting module for the Center for Continuing Education at the Pontifical Catholic University of Ecuador, Ibarra Campus (PUCE-SI). This center, dedicated to continuing education in languages and various areas of knowledge, seeks to respond to the demands of the labor market and promote professional development. However, it lacks a comprehensive system for managing its consulting services. This deficiency negatively impacts operational efficiency, decision-making, and responsiveness to customer needs, hindering project monitoring, resource optimization, and information management. To address these problems, this project proposes the development of a consulting module that will be integrated into the management system of the Center for Continuing Education. This module will allow for the standardization of consulting processes, defining clear and consistent workflows for the different stages of a project, from the creation of clients to the monitoring of the consultancy by status and the generation of reports. The development of the consulting module will be based on the Scrum methodology, an agile approach that promotes flexibility, collaboration, and incremental value delivery. Technologies such as TypeScript, Vue.js, PostgreSQL, and Docker will be used to ensure efficiency, scalability, and system security. It is expected that the implementation of this consulting module will contribute to improving the operational efficiency of the Center for Continuing Education by optimizing processes, reducing management times, and facilitating collaboration between the different actors involved.